Metabolome and Transcriptome Analyses of Anthocyanin Accumulation Mechanisms Reveal Metabolite Variations and Key Candidate Genes Involved in the Pigmentation of Prunus tomentosa Thunb. Cherry Fruit - Zhang, Aidi; Yang, Haiying; Ji, Shujun; Tian, Changping; Chen, Ni; Gong, Hansheng; Li, Jianzhao (Frontiers in Plant Science, 2022)
Prunus tomentosa Thunb. has excellent nutritional, economic, and ornamental values with different fruit color. The red coloration of fruit is determined by anthocyanin pigmentation, which is an attractive trait for consumers. However, the mechanisms underlying fruit color formation in the P. tomentosa cherry are not well understood. In this research, the pigmentation patterns in red-color P. tomentosa (RP) fruit and white-color P. tomentosa (WP) were evaluated. Anthocyanin content in matured RP fruit was significantly abundant compared with WP fruit. Metabolomic profiling revealed that pelargonidin 3-O-glucoside, cyanidin 3-O-rutinoside, and pelargonidin 3-O-rutinoside were the predominant anthocyanin compounds in the RP fruit, while, WP fruit had less anthocyanin compositions and lower level. Then, integrative analyses of transcriptome and metabolome identified 285 significant differentially expressed genes (DEGs) closely related to anthocyanin differentially expressed metabolites (DEMs). Among them, nine genes were involved in anthocyanin biosynthesis, transport and degradation pathway, including four biosynthesis genes (PtPAL1, PtDFR, PtANS, PtUFGT), two transport genes (PtGST11, PtABC10), and three degradation genes (PtPOD1, PtPOD16, PtPOD73). Transcriptome data and real-time PCR showed that the transcript levels of biosynthesis and transport genes were significantly higher in RP than in WP, especially PtANS, PtUFGT, and PtGST11, suggesting they may play key roles in red-colored fruit formation. Meanwhile, the degradation related genes PtPOD1/16/73 took on exactly opposite trend, suggesting their potential effects on anthocyanin degradation. These results provide novel insights into color patterns formation mechanisms of cherries fruit, and the candidate key genes identified in anthocyanin biosynthesis, transport and degradation may provide a valuable resource for cherry breeding research in the future.